2017
DOI: 10.1186/s13013-017-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Results of ultrasound-assisted brace casting for adolescent idiopathic scoliosis

Abstract: BackgroundFour factors have been reported to affect brace treatment outcome: (1) growth or curve based risk, (2) the in-brace correction, (3) the brace wear quantity, and (4) the brace wear quality. The quality of brace design affects the in-brace correction and comfort which indirectly affects the brace wear quantity and quality. This paper reported the immediate benefits and results on using ultrasound (US) to aid orthotists to design braces for the treatment of scoliosis.MethodsThirty-four AIS subjects part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…This provided quantitative applied pressures and real-time simulated in-brace correction for the orthotist to assess the brace design. Literature had shown that fewer brace adjustments clinic visits were required with ultrasound assisted brace casting ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provided quantitative applied pressures and real-time simulated in-brace correction for the orthotist to assess the brace design. Literature had shown that fewer brace adjustments clinic visits were required with ultrasound assisted brace casting ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…This process took <1 min. This US assisted method had been demonstrated to provide a radiation-free method to determine the optimum pressure level and location to assist brace design, resulting in decreased radiation exposure during follow-up brace evaluation, increased the in-brace correction, reduced the patients' visits to both brace adjustment and scoliosis clinics ( 16 , 17 ). The orthotist then decided if altering bolster locations and orientations and pressure levels might improve correction.…”
Section: Methodsmentioning
confidence: 99%
“…However, to prevent too much radiation exposure, the more in-brace correction X-ray was not recommended. A study by Lou et al [26] suggested utilizing ultrasound in assisting brace casting and in-brace correction monitoring while reducing radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A pneumatic bracing simulation system (Figure 1) was developed to simulate the classic three-point corrective forces system of CB referring to the Providence brace system 14 and Fixation, Elongation, Derotation system. 17 In a cuboid frame, a pair of underarm pallets and pelvic baffles were designed to fix both arms and the pelvis.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent research further affirmed the role of ultrasound evaluation in optimizing the magnitude and position of the corrective forces in brace fabrication. 14 Although these studies proved the function of ultrasound in optimizing brace design, generally applicable schemes of pressure positions for AIS have not been reported.…”
Section: Introductionmentioning
confidence: 97%